2012
DOI: 10.1002/anie.201108010
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Control over Liquid Surface Properties with Responsive Surfactants

Abstract: Droplet attraction: Surfactants responsive to magnetic fields are reported for the first time. This new class of magnetic ionic liquid surfactants (MILSs; see picture) shows remarkable effects on surface and interfacial tension and allows access to magneto‐responsive emulsions and new methods of separation, recovery, catalysis, and potential magnetophoretic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
238
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(257 citation statements)
references
References 27 publications
14
238
3
2
Order By: Relevance
“…In that context it might also be mentioned that ''magnetic surfactants'' have received high attention very recently. 28 Accordingly, self-assembly in MRTIL is an interesting question and in this work we describe the formulation of a magnetic microemulsion based on a MRTIL, which to the best of our knowledge, is the first time that such a system is described. Other microemulsions with magnetic properties are all based on microemulsions containing magnetic inorganic nanoparticles, which is a very different type of formulation.…”
Section: Introductionmentioning
confidence: 99%
“…In that context it might also be mentioned that ''magnetic surfactants'' have received high attention very recently. 28 Accordingly, self-assembly in MRTIL is an interesting question and in this work we describe the formulation of a magnetic microemulsion based on a MRTIL, which to the best of our knowledge, is the first time that such a system is described. Other microemulsions with magnetic properties are all based on microemulsions containing magnetic inorganic nanoparticles, which is a very different type of formulation.…”
Section: Introductionmentioning
confidence: 99%
“…1 These magneto-responsive surfactants are based on common cationic surfactants with metal complex anions, which, because they contain high effective concentrations of metal centres, allow physico-chemical properties to be controlled non-invasively and reversibly by external magnetic fields. Surprisingly, even dilute micellar solutions of these paramagnetic surfactants exhibit a magnetic response, opening up new possibilities for control over interfaces, dispersions, colloids and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[8] In 2014, Degen et al investigated organic surfactants with paramagnetic FeCl 4 À as acounterion and concluded that there is no special "magnetic surfactant effect".…”
mentioning
confidence: 99%
“…[8] In 2014, Degen et al investigated organic surfactants with paramagnetic FeCl 4 À as acounterion and concluded that there is no special "magnetic surfactant effect". [9] This last study motivated us to invest effort in preparing compounds in which the transition-metal species is an integral part of the head group.…”
mentioning
confidence: 99%